Students' Strategies to Overcome The Level of Language Anxiety in Speaking Performance at UPT SMP Negeri 13 Gresik - Khoiriyah, Nurul; Mufidah, Zahratul Maujudatul (Critical Review of English-Arabic World Journal, 2022)
The objectives of this research to find out the factors caused the students’ anxiety in speaking performance and to find out the students’ strategies to overcome the level of language anxiety in speaking performance. The research applied a qualitative descriptive as research method. It was conducted in UPT SMPN 13 Gresik. The data were gathered by questionaire, observations and interview. While, technique and data source triangulation were used to validate data. The results of this study indicate that not all levels of language anxiety are experienced by students.